The Effect of Using Different Probiotic Products in Biofloc Systems on the Growth of Snakehead (Channa striata) - Zahlan, Alfadita; Rusliadi, Rusliadi; Putra, Iskandar (Jurnal Perikanan dan Kelautan, 2025)
Snakehead (Channa striata) is one of the popular freshwater commodities in Indonesia, but its cultivation is still relatively low due to its relatively slow growth. Biofloc technology, which relies on microorganisms such as probiotic bacteria, is a potential solution to increase cultivation efficiency. This study aims to evaluate the effect of using various types of probiotics in the biofloc system on the growth of cork fish and to determine which type of probiotic is most effective. The research was conducted at the Cultivation Technology Laboratory, Department of Aquaculture, Faculty of Fisheries and Marine, Universitas Riau, for 56 days from August to October 2024. The method used was experimental with a completely randomized design (CRD), using four treatments (P0 = control, P1 = Probio-7, P2 = Multi-Cell, P3 = Aquaenzyme) and three replications. The results showed that probiotics had a significant effect on growth parameters. The best treatment was P2 (probiotic Sel Multi), which produced the highest absolute weight (2.97 g), absolute length (3.63 cm), specific growth rate (2.02%), lowest feed conversion ratio (1.65), and highest survival rate (86.66%).